2022
DOI: 10.1177/08862605211073104
|View full text |Cite
|
Sign up to set email alerts
|

Family Sex Trafficking Among the Bedia Caste of India: Defying the Dominant Human Trafficking Discourse

Abstract: Largely characterized as an urban issue, empirical studies of minor sex trafficking in rural communities—including India, a global hotspot for child sex trafficking—are exceptionally uncommon. Yet, the commercial sexual exploitation of children thrives in many rural Indian villages, fueled by caste discrimination, family tradition, and poverty. In response, this study aimed to investigate minor sex trafficking among a particular culturally unique and geographically isolated population, in relation to the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…A substantial body of research has linked sexual exploitation to economic vulnerabilities, such as poverty, low parental education, debts, financial insecurity, material need, and lack of economic opportunities (n = 17). Notable is that most studies involved non-Western countries, such as India, Mexico, Uganda, Nigeria, and Rwanda (Acharya & Bryson Clark, 2021;Dalla et al, 2020Dalla et al, , 2022Goldenberg et al, 2015;Kiss et al, 2022;Macias-Konstantopoulos et al, 2013;Njoku et al, 2022;Rocha-Jimenez et al, 2018;Silverman et al, 2007;Williams et al, 2012Williams et al, , 2018. In these countries, economic vulnerabilities were more often characterized as environmental factors such as a lack of educational or labor opportunities in the environment and a lack of resources due to migration or living in refugee camps.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A substantial body of research has linked sexual exploitation to economic vulnerabilities, such as poverty, low parental education, debts, financial insecurity, material need, and lack of economic opportunities (n = 17). Notable is that most studies involved non-Western countries, such as India, Mexico, Uganda, Nigeria, and Rwanda (Acharya & Bryson Clark, 2021;Dalla et al, 2020Dalla et al, , 2022Goldenberg et al, 2015;Kiss et al, 2022;Macias-Konstantopoulos et al, 2013;Njoku et al, 2022;Rocha-Jimenez et al, 2018;Silverman et al, 2007;Williams et al, 2012Williams et al, , 2018. In these countries, economic vulnerabilities were more often characterized as environmental factors such as a lack of educational or labor opportunities in the environment and a lack of resources due to migration or living in refugee camps.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Other negative experiences at the societal level concerned gender, social, and cultural inequalities (n = 5); normalization of sex trade in the environment (n = 3); a failing legal system (n = 2); and terrorism (n = 1) and were mainly found in non-Western countries such as India, Brazil, and Nigeria (Dalla et al, 2020(Dalla et al, , 2022Digidiki & Bhabha, 2018;Jani & Felke, 2017;Macias Konstantopoulos et al, 2013;Njoku et al, 2022;Silverman et al, 2007;Williams et al, 2012). These studies predominantly involved females and no gender comparisons were made.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The commercial sexual exploitation of children (CSEC) is a socially accepted form of prostitution by numerous Indian castes. Girls as young as 12 are selected to enter the sex industry to generate family income [32][33][34]. By making their own lives worse, Bedia girls engaged in prostitution improve the lives of their siblings and parents [32].…”
Section: Introductionmentioning
confidence: 99%
“…Many cases have been reported where Bedia girls have been rescued from a sex trafficking situation, handed over to their parents, and compelled again to go into sex work [35]. While some studies on vulnerabilities to sex trafficking among Bedia youth concluded that birth order did not predict commercial sex industry entry among female siblings [33], other studies concluded that the eldest daughter was often the one selected to enter the commercial sex trade. Rana et al [34] concluded that "The queerness of the Bedia community is that they themselves train their girls to be prostitutes.…”
Section: Introductionmentioning
confidence: 99%